MENINGKATKAN KEMAMPUAN MENGENAL WARNA DASAR BAGI ANAK TUNAGRAHITA RINGAN X MELALUI PERMAINAN KOLASE di SLB PERWARI PADANG - Dwi Oktasesa, Damri, Asep Ahmad Sopandi (Universitas Negeri Padang, 2013)
This research is motivated by problems of mild mental retardation children in special-ed-classes D/C1 Perwari Padang who have problems in recognizing basic colors (red, yellow and blue). This study aims to prove the effective eness of he game collage color to enhance the ability to know the basis for mental retardation children .This research using the Single Subject Research (SSR), the A-B design and data analysis techniques using visual analysis chart. The results showed, mild mental retardation in a child's ability to know the basic color increases.